Effectiveness of Integrative Systemic-Psychodynamic-Behavioral Couples Therapy on Marital Quality of Life in Dysfunctional Couples Referred to Counseling Centers - Pourmeydani, Somayeh; Mehrabizadeh Honarmand, Mahnaz; Hashemi, Seyyed Esmaiel; Abbaspour, Zabihollah (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The aim of this study was to evaluate the effectiveness of integrative systemic-psychodynamic-behavioral couples therapy on marital quality of life in dysfunctional couples referred to counseling centers in Ahvaz.Methods: The research design was a single-case experimental design. The study population included all dysfunctional couples who visited counseling centers in Ahvaz in 2019. A convenience sampling method was used, selecting three couples with low marital quality of life, who then received integrative systemic-psychodynamic-behavioral couples therapy over 12 sessions, each lasting 1.5 hours. The Perceived Marital Quality Dimensions Questionnaire (Fletcher et al., 2000) was used in this study. To analyze the data, visual analysis, the stability index, and the percentage of improvement were used.Findings: The results showed that the stability index during both the treatment and follow-up phases was significant. The overall percentage of improvement also indicated that the effectiveness of integrative systemic-psychodynamic-behavioral therapy on marital quality of life in dysfunctional couples, based on Blanchard’s classification, fell within the "slight improvement" category during both the treatment and follow-up phases, which generally suggested the success of the intervention in improving marital quality of life in dysfunctional couples.Conclusion: Based on the findings, it can be concluded that integrative systemic-psychodynamic-behavioral couples therapy can lead to an improvement in marital quality of life.